The Effect of Human Resource Quality, Work Motivation, and Employee Engagement on The Performance of Experts of The House of Representatives of The Republic of Indonesia with The Certainty of Leadership Status as A Moderation Variable - Ramli, Rusli; Firman, Ahmad; Latief, Fitriani (SAFE-Network, 2026)
This study aims to analyze the influence of human resource quality, motivation, and employee engagement on the performance of Experts of the House of Representatives of the Republic of Indonesia, with the certainty of personnel status as a moderating variable. The research method is a quantitative, employing Structural Equation Modeling (SEM) with Partial Least Squares (PLS) via SmartPLS 4.0. Data was obtained through the distribution of questionnaires to Experts of the House of Representatives of the Republic of Indonesia. The results of the study show that the quality of human resources, motivation, and employee engagement have a positive and significant effect on the performance of the Experts of the House of Representatives of the Republic of Indonesia. In addition, the certainty of employment status has been shown to moderate the relationship between human resource quality, motivation, and employee engagement and performance, thereby strengthening the influence of these three variables. Theoretically, this study strengthens the Job Demands–Resources (JD–R) Theory, by showing that the quality of human resources as personal resources as well as motivation and employee engagement, as part of the motivational process, contribute significantly to performance. In addition, the certainty of employment status acts as a job resource that strengthens the relationship between individual resources and performance, thereby enriching the literature on performance determinants in the public sector. This research emphasizes the importance of improving the quality of human resources, strengthening work motivation, and increasing employee engagement in an effort to improve the performance of the Experts of the House of Representatives of the Republic of Indonesia. On the other hand, the certainty of employment status is a strategic factor that can strengthen the effectiveness of these three variables in producing optimal performance.